Analisis Keunggulan Komparatif: Studi Perbandingan Nilai Ekspor Antara Sulawesi Tengah dan Sulawesi Barat dalam Perdagangan Global - Riady Ibnu Khaldun; Muhammad Sajidin; Danar H.A Wardhana; Rezky RA (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Provinsi Sumatera Utara, 2026)
This study aims to examine the comparative export values of key commodities between Central Sulawesi Province and West Sulawesi Province in the context of global trade. Both provinces are located in the same region, namely Sulawesi Island, and are geographically adjacent. However, they possess distinct economic characteristics and leading sectors, as reflected in the main commodities they export to international markets. This research uses secondary data obtained from various official sources, such as publications by the Central Statistics Agency (BPS), relevant government institutions, and credible online sources. The method employed is a qualitative descriptive approach, focusing on export data over a five-year period from 2018 to 2022. The data are analyzed and presented in tables and graphs to provide a clear illustration of trends and comparative export values between the provinces. The findings reveal that Central Sulawesi Province has a comparative advantage in Iron and Steel commodities, which account for approximately 65% of the province's total export value. In contrast, West Sulawesi Province demonstrates a dominant export in Animal or Vegetable Fats and Oils, contributing 90.62% of its total exports. In terms of value, the average exports of Central Sulawesi during the study period reached US 9,927 million, significantly surpassing West Sulawesi’s average of only US 502 million. These findings highlight a significant difference in export structure and economic potential between the two provinces in the landscape of global trade.